Sacred Space and Faith Expression: Centering on the Daoist Stelae of the Northern Dynasties - Yuan Zhang (Religions, 2025)
This paper examines the Daoist stelae of the Northern Dynasties through the lens of Eliade’s religious theory, with particular focus on the transformation of profane objects into sacred ones and the transition of local believers from the profane to the sacred. Utilizing Eliade’s notions of “symbol”, “myth”, and “sacred space”, this study investigates two critical dimensions of the Daoist stelae. First, it analyzes their visuality by closely examining the imagery and symbolic systems presented on the stelae—namely, the “mythical pattern” identified by Eliade—with particular attention to representations of the main deity, the Heavenly Palace, and the Xiwangmu Xianjing (Queen Mother of the West’s transcendent realm). Second, it addresses their materiality by reconstructing the invisible processes associated with the stelae, focusing on the formation of sacred space and the Daoist rituals enacted therein. Applying phenomenology of religion to Daoist stelae analysis helps compensate for the limitations of extant Daoist scriptures and official historical records.